Dinámicas de las estrategias de afrontamiento de una adulta joven diagnosticada con ansiedad y depresión durante el confinamiento COVID 19 en Cartago Valle (2021)
The general objective of the present work is to understand the dynamics of the coping strategies of a young adult diagnosed with anxiety and depression, during the COVID 19 confinement in Cartago Valle del Cauca in 2020; For this, the qualitative methodology with a case study design was used, the main instrument of which was a semi addition to the review of structured interview, in the participant's medical history.